Nikkatsu Diamond Guys - Volume 1 - Suzuki, Seijun; Masuda, Toshio; Saito, Buichi (Arrow Video, 2016)
Nikkatsu, the oldest film studio in Japan, inaugurated a star system in the late 1950s, finding talent and contracting to their Diamond Line for a series of wild genre pictures. This collection celebrates these Diamond Guys with three classic films from directors Seijun Suzuki (Branded to Kill), Toshio Masuda (Rusty Knife) and Buichi Saito (Lone Wolf and Cub: Baby Cart in Peril). [Cover]